1983
DOI: 10.1148/radiology.148.1.6856836
|View full text |Cite
|
Sign up to set email alerts
|

The traumatized scrotum. Ultrasound evaluation.

Abstract: Testicular salvage rates are improved markedly when surgical correction of a ruptured tunica albuginea is performed within 72 hours after a scrotal injury. The authors studied 11 patients who had suffered various types of blunt or penetrating trauma to the scrotum. The importance of ultrasound for the evaluation of the traumatized scrotum and detection of a testicular rupture is stressed. The spectrum of abnormalities that may be present after a scrotal injury is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…A few years later, Gross [24] reported that the probability of testicular salvage after blunt trauma decreased from 80% to 32% if the exploration was delayed by more than 3 days. Jeffrey et al [16] and Lupetin et al [25] similarly reported the rate of testicular salvage to be 90% when explored within 72 h, and only 45% when surgery was delayed by > 72 h.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A few years later, Gross [24] reported that the probability of testicular salvage after blunt trauma decreased from 80% to 32% if the exploration was delayed by more than 3 days. Jeffrey et al [16] and Lupetin et al [25] similarly reported the rate of testicular salvage to be 90% when explored within 72 h, and only 45% when surgery was delayed by > 72 h.…”
Section: Managementmentioning
confidence: 99%
“…Scrotal ultrasonography (SUS) is the most sensitive and specific imaging method for detecting intrascrotal injury (Level of evidence, LOE, 2) [10][11][12][13]. The primary goal of SUS is to assess the integrity and vascularity of the testes.…”
Section: © 2 0 0 4 B J U I N T E R N a T I O N A Lmentioning
confidence: 99%
“…If it is not repaired within 72 hours, orchiectomy may be required in greater than 50% of patient^.^^,^^ If more urgent surgical intervention occurs in less than 72 hours, a greater than 80% salvage rate has been r e p~r t e d .~~,~' ,~~ Varying opinions exist as to the ability of ultrasound to detect testicular rupture. The grayscale findings described with testicular rupture include disruption of the tunica albuginea (noted as a discontinuity of the normally echogenic rim), poorly defined testicular margins, and focal hyperechoic or hypoechoic areas in the testicular parenchyma (Figures 24, 25).41- 47 The accuracy of ultrasound in diagnosing the presence or absence of rupture has varied in the literature. Fournier et a1 reported a 94% success rate in predicting the presence of testicular rupture.…”
mentioning
confidence: 99%
“…In the event of a traumatized scrotum, SUS can confirm the integrity of the tunica albugenia to avoid unnecessary scrotal exploration. 15 Conversely the patient can be informed of the likely removal of the testis at exploration when there are features of an injured tunica albuginea. SUS can also detect an hematocele, which calls for exploration, unlike a scrotal wall hematoma.…”
Section: Discussionmentioning
confidence: 99%